Molecular Characterization of the Onset and Progression of Colitis in Inoculated Interleukin-10 Gene-Deficient Mice: A Role for PPARα - Bianca Knoch; Matthew P. G. Barnett; Janine Cooney; Warren C. McNabb; Diane Barraclough; William Laing; Shuotun Zhu; Zaneta A. Park; Paul MacLean; Scott O. Knowles; Nicole C. Roy (PPAR Research)
The interleukin-10 gene-deficient (Il10-/-) mouse is a model of human inflammatory bowel disease and Ppara has been identified as one of the key genes involved in regulation of colitis in the bacterially inoculated Il10-/- model. The aims were to (1) characterize colitis onset and progression using a histopathological, transcriptomic, and proteomic approach and (2) investigate links between PPARα and IL10 using gene network analysis. Bacterial inoculation resulted in severe colitis in Il10-/- mice from 10 to 12 weeks of age. Innate and adaptive immune responses showed differences in gene expression relating to colitis severity. Actin cytoskeleton dynamics, innate immunity, and apoptosis-linked gene and protein expression data suggested a delayed remodeling process in 12-week-old Il10-/- mice. Gene expression changes in 12-week-old Il10-/- mice were related to PPARα signaling likely to control colitis, but how PPARα activation might regulate intestinal IL10 production remains to be determined.